Beef Longissimus Lumborum Steak pH Affects External Bioelectrical Impedance Assessment - F. Najar-Villarreal; E. A. Boyle; T. A. Houser; C. I. Vahl; J. Wolf; J. M. Gonzalez; T. G. O'Quinn; J. Kastner; M. D. Chao (Kansas Agricultural Experiment Station Research Reports, 2020)
Objective:To use external bioelectrical impedance analysis to assess postmortem chemical changes in normal- and high-pH beef longissimus lumborum steaks during simulated retail display. Study Description:Beef strip loins (n = 20; postmortem age = 14 d) obtained from a commercial processor were sorted into two treatments, normal-pH (5.61–5.64; n = 11) and high-pH (6.2–7.0; n = 9). Loins were fabricated into five 1-inch thick steaks (n = 100), and randomly assigned to one of five display days: 1, 3, 5, 7, and 9. External bioelectrical impedance values, oxygen consumption, metmyoglobin reducing ability, protein degradation, water holding capacity, and pH were assessed on each storage day. The BottomLine:External bioelectrical impedance is a method that could be used to separate normal- and high-pH strip loins with potential for rapid, in-plant use to identify dark-cutting beef.
Keywords: Beef; external electrical impedance; pH; postmortem